A Low Membrane Hsp70 Expression in Tumor Cells With Impaired Lactate Metabolism Mediates Radiosensitization by NVP-AUY922 - Schwab, Melissa; Multhoff, Gabriele (Frontiers in Oncology, 2022)
As overexpression and membrane localization of stress proteins together with high lactate levels promote radioresistance in tumor cells, we studied the effect of the Hsp90 inhibitor NVP-AUY922 on the cytosolic and membrane expression of heat shock proteins (HSPs) and radiosensitivity in murine melanoma (B16F10) and human colorectal (LS174T) wildtype (WT) and lactate dehydrogenases A/B double knockout (LDH−/−) tumor cells. Double knockout for LDHA/B has been found to reduce cytosolic as well as membrane HSP levels, whereas treatment with NVP-AUY922 stimulates the synthesis of Hsp27 and Hsp70, but does not affect membrane Hsp70 expression. Despite NVP-AUY922-inducing elevated levels of cytosolic HSP, radiosensitivity was significantly increased in WT cells and even more pronounced in LDH−/− cells. An impaired lipid metabolism in LDH−/− cells reduces the Hsp70 membrane-anchoring sphingolipid globotriaosylceramide (Gb3) and thereby results in a decreased Hsp70 cell surface density on tumor cells. Our results demonstrate that the membrane Hsp70 density, but not cytosolic HSP levels determines the radiosensitizing effect of the Hsp90 inhibitor NVP-AUY922 in LDH−/− cells.